2018
DOI: 10.1002/pi.5621
|View full text |Cite
|
Sign up to set email alerts
|

Biobased epoxy resin derived from eugenol with excellent integrated performance and high renewable carbon content

Abstract: Developing biobased epoxy resin with high renewable carbon content and outstanding integrated performance is beneficial for both sustainable development and applications in cutting-edge fields. Herein, a biobased epoxy monomer (TEUP-EP) with high renewable carbon content (100%) was synthesized from renewable eugenol with a sustainable process; TEUP-EP was then blended with 4,4 ′ -diaminodiphenylmethane (DDM) to develop a new biobased epoxy resin (TEUP-EP/DDM). The integrated performance of TEUP-EP/DDM resin wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
29
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(31 citation statements)
references
References 51 publications
2
29
0
Order By: Relevance
“…Liu et al [25] took advantage of the phenol group for connecting two eugenol moieties by reaction with 1,4-dibromobutane and further epoxidation of allyl groups to get a diepoxy monomer. In addition, a trimer from eugenol was synthesized by reacting it with phosphorous oxychloride followed by further epoxidation [26]. This tripoxy monomer was cured with 4,4'-diaminodiphenylmethane and the thermoset obtained was compared with the one obtained from DGEBA, reaching the eugenol derivative better performances.…”
Section: Of 12mentioning
confidence: 99%
“…Liu et al [25] took advantage of the phenol group for connecting two eugenol moieties by reaction with 1,4-dibromobutane and further epoxidation of allyl groups to get a diepoxy monomer. In addition, a trimer from eugenol was synthesized by reacting it with phosphorous oxychloride followed by further epoxidation [26]. This tripoxy monomer was cured with 4,4'-diaminodiphenylmethane and the thermoset obtained was compared with the one obtained from DGEBA, reaching the eugenol derivative better performances.…”
Section: Of 12mentioning
confidence: 99%
“…In a previous study, we also showed that the use of a phosphorus containing monomer synthesized with three eugenol residues led to the enhancement of the stability of epoxy thermosets, [32] which has been confirmed in a following study investigating flame retardancy properties. [33] Moreover, it has been showed that the use of a phosphorus-containing allylated monomer can enhance the properties of BMI thermosets. [34] Recently, it has been shown that an eugenol-based phosphate is a suitable monomer for the synthesis of bismaleimide thermosets with flame retardant properties.…”
Section: Introductionmentioning
confidence: 99%
“…16 Currently, epoxy resins play an indispensable role in various elds, such as coatings, aerospace, adhesives, paints, and engineering plastics. [17][18][19] Up to now, there were few literatures relevant to the fabrication of microcapsules/microspheres using epoxy resins as shells. [20][21][22] Recently, we synthesized MCs with porous surface using epoxy resin and demonstrated that epoxy resin based MCs prepared with a high epoxy value tended to yield a higher crosslinking degree, less porosity and a better thermal stability.…”
Section: Introductionmentioning
confidence: 99%